PENGUATAN DAN PENDAMPINGAN WIRAUSAHA MAHASISWA SEBAGAI UPAYA MENDORONG TUMBUHNYA PENGUSAHA MUDA DI LINGKUNGAN PERGURUAN TINGGI - Sukini Sukini; Hermien Nugraheni; Prasko Prasko (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2024)
Entrepreneurship education is realized through carefully designed and structured hands-on entrepreneurial practices. This practice can be in the form of product manufacturing or service provision. This program aims to create young entrepreneurs from among students who are able to create jobs for many people. The entrepreneurial strengthening and mentoring program is carried out using the method of empowering students as young business actors. The program is carried out through three stages, namely the preparation, implementation and evaluation stages. The activity begins with coordination with related parties, implementation of strengthening and mentoring by lecturers and the Office of Cooperatives and MSMEs. Entrepreneurship assistance for students is able to encourage the growth of young entrepreneurs in the Poltekkes Kemenkes Semarang environment and increase the activities of the honesty canteen to become a Multipurpose Cooperative Kopma "Hygienic Snacks".